Epidemiology of hypertension among patients with type 2 diabetes in the Democratic Republic of Congo - Xoliswa Simelane; Jean-Pierre Fina-Lubaki; Joel M. Francis (African Journal of Primary Health Care & Family Medicine)
Background: Hypertension is a common comorbidity among patients with type 2 diabetes (T2D) and is associated with poorer treatment outcomes.